Reconnaissance of the Function of Social Media on Study Habits Of Undergraduate Students in the University of Cape Coast. - Annan-Brew, Ruth Keziah; Nartey, Philip (International Journal of Scientific Research and Management (IJSRM), 2021)
The world today is celebrating the improvements in communication technology which has broadened the scope of communication through Information and Communication Technologies (ICTs). Modern Technology in communication no doubt has turned the entire world into a “Global village”. But as it is, technology like two sides of a coin, bring with it both negative and positive sides. The study examined the function of social media on students’ study habit. The study employed a descriptive survey design with a quantitative approach. The stratified and purposive sampling techniques were used to select 217 out of 245 students from level 300(n=111) and 400(n=106)) undergraduate Psychology students. Researchers’-designed questionnaire titled “Usage of Social Media Questionnaire” (USMQ) and ‘‘Students Study Habits Questionnaire” (SSHQ) with Cronbach's Alpha reliability coefficients of 0.74 and 0.83 respectively were used to collect data for the study. WhatsApp and Facebook were the predominant social media sites students were exposed to. Students were found to be addicted to social media usage. The study revealed no statistically significant differences in the usage of social media with regards to gender and age. Social media was found to significantly influence the study habits of respondents. Specifically, increased usage of social media resulted in negative study habit. It was recommended that academic counsellors together with the management of tertiary institutions should map out strategies (eg., integration of topics on the pros and cons of social media use in the lecture theatre in various courses of study by lecturers and restriction of social media use during lectures by students) to reduce students’ addiction to social media platforms. It also recommended to students to allow quality time for studies and use of social media for the right purposes, especially their academic studies.